Тиристоры Справочник - Григорьев О. П. Олег Петрович; Замятин В. Я. Владимир Яковлевич; Кондратьев Б. В. Борис Владимирович; Пожидаев С. Л. Сергей Леонидович (Массовая радиобиблиотека Вып. 1155)
Авт. указ. на обороте тит. л.